Usage of Causative Verbs in Different Contexts - Ravshanjonovna, Karimjonova Shahlo (Jurnal Multidisiplin Madani, 2024)
Causative verbs are an essential part of the English language, allowing speakers to describe the act of causing something to happen. This paper provides an overview of causative verbs in English, their various forms and uses, and some common misconceptions about their usage. The paper also explores how causative verbs can be used in different tenses and how they interact with modal verbs. Finally, the paper examines the use of causative verbs in passive voice constructions